PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KINERJA MANAJERIAL SEBAGAI VARIABEL MODERATING - Setyawan, Hari; Tanjung, Amries Rusli; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of directly variable budget goal clarity, accounting controls and compliance with laws and regulations as well as the influence of these variables on performance accountability of government agencies dimederasi by variable managerial performance, the study was conducted in Kampar regency precisely in the regional work units Kampar, with consideration facilitate researchers in data collection. The population in this study is mandatory LAKIP agencies Kampar Regency in Riau Province. The sample in this study is the Working Device Unit (SKPD) Kampar District, represented by the Head of Finance, treasurer and Chief of Staff, Government Agencies Program. Type of this research is the primary data. The method the researchers used multiple linear regression. The results in this study indicate that the budget goal clarity, accounting controls and compliance with laws and regulations have pesitif influence on performance accountability of government agencies and the interaction between the independent variables and managerial performance positive effect on performance accountability of government agencies. In this study, the independent variables are only able to affect 60% of the remaining dependent variable is influenced by other variables that are not described in this study.Keywords : Budget, Controls, Regulations, Accountability and Performance